PENERAPAN METODE FUZZY INFERENCE MAMDANI DALAM SELEKSI KARYAWAN KONTRAK PT KREASI UTAMA MANDIRI - Pameswary, Nathasya; Puspasari, Shinta; Ramadhan, Mustafa (Universitas Islam Balitar, 2024)
This study aims to improve the performance of the employee selection system. This research uses the Mamdani Fuzzy Inference System to determine the suitability of job applicants for the company. Recommendations for job applicants can be used as a reference for selecting permanent employees. The common problem in selecting permanent employees is the difficulty for the company in assessing and selecting competent job applicants, as the company has to compare the test results of each job applicant one by one, requiring a long time. In addition, the most difficult thing in making decisions is eliminating someone's subjectivity, so that every decision made is objective based on the criteria expected by the company. The results of this study proved that by applying mamdani fuzzy inference to the selection of contract employees at PT. Kreasi Utama Mandiri can facilitate management in selecting contract employees with an accuracy of 90% when compared to HRD assessments.